The Study of Entrepreneurship Ecosystem in Lao PDR - LATTANASOUVANNAPHONH, Champa; SOMSAMONE, Vilayphone; SOULIYASACK, Somkit; SISAVANH, Orlathai; KINGSADA, Youthasack; KHOMTHAVONG, Phonepasith (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study is to 1) understand an overview of entrepreneurship and 2) identify the entrepreneurial ecosystem of Lao PDR in Luang Prabang. The Focus-group discussion (FGD) qualitative method was designed for this study. The key informants of eight stakeholders were selected from Government Departments, entrepreneurial Associations, academic lecturers, and companies in Luang Prabang. The overview of entrepreneurship was defined based on the perspective of local stakeholders and the current ecosystem of Entrepreneurship in Luang Prabang is human capital and finance. Human capital is a very important component as it requires high levels of entrepreneurship and management skill to be able to access regional and international market. Entrepreneurship education is really necessary to respond to the government policy by reducing the quotas for government employment and increasing self-employment. Our assumption that finance is the first challenges for entrepreneurship in Lao PDR. However, the finance is the second important factor when he or she wants to expand business activities